Does Exercise Influence the Susceptibility to Arterial Thrombosis? An Integrative Perspective - Olsen, Line Nørregaard; Fischer, Mads; Evans, Phillip Adrian; Gliemann, Lasse; Hellsten, Ylva (Frontiers in Physiology, 2021)
Arterial thrombosis is the primary cause of death worldwide, with the most important risk factors being smoking, unhealthy diet and physical inactivity. However, although there are clear indications in the literature of beneficial effects of physical activity in lowering the risk of cardiovascular events, exercise can be considered a double-edged sword in that physical exertion can induce an immediate pro-thrombotic environment. Epidemiological studies show an increased risk of cardiovascular events after acute exercise, a risk, which appear to be particularly apparent in individuals with lifestyle related disease. Factors that cause the increased susceptibility to arterial thrombosis with exercise are both chemical and mechanical in nature and include circulating catecholamines and vascular shear stress. Exercise intensity plays a marked role on such parameters, and evidence in the literature accordingly point at a greater susceptibility to thrombus formation at high compared to light and moderate intensity exercise. Of importance is, however, that the susceptibility to arterial thrombosis appears to be lower in exercise-conditioned individuals compared to sedentary individuals. There is currently limited data on the role of acute and chronic exercise on the susceptibility to arterial thrombosis and many studies include incomplete assessments of thrombogenic clotting profile. Thus, further studies on the role of exercise, involving strong biomarkers, are clearly warranted.